Evaluating gold mining in Ranowulu between CSR benefits and social vulnerability - Meijina Exreana Karundeng; Michael Mamentu; Burhan Niode (Advances in Community Services Research, 2026)
Abstract Purpose: This study evaluates the social impacts of PT. Tambang Tondano Nusajaya gold mining activities on communities in Ranowulu District, Bitung City, North Sulawesi. Research Method: An exploratory descriptive qualitative design was applied through semi-structured interviews, field observation, and documentation involving one corporate representative and four ring-1 residents. Results and Discussion: Mining generates local employment, skills training, micro-enterprise opportunities, educational support, and infrastructure assistance. However, residents also report land conversion, dust, blasting vibration, cracked houses, health concerns, passive participation, and dependence on company-driven economic circulation. Implications: The study recommends participatory social impact assessment, independent monitoring by DLH Kota Bitung and Dinas PUPR Kota Bitung, transparent grievance mechanisms, and livelihood diversification beyond mining. Originality: This article integrates outcome evaluation, process evaluation, CSR fit, social license to operate, and social impact assessment to show that mining legitimacy depends on balancing benefits, operational-risk mitigation, and meaningful participation.